Comparison of Student's Learning Success Between Problem Solving Methods and Recitations in Learning Public Relations and Protocollability (Economic Education Analysis Journal, 2022)
This study aimed to determine the difference in the level of student learning success using the Problem-Solving method and the Recitation method in learning Automation of Public Relations and Protocol Governance at SMK Negeri 3 Padang using Quasi-Experimental type with Noneequivalent Control Group Design. The population of this study was 61 students with a sample of all parts of the population. The sampling technique was Total Sampling. The research instrument was in the form of test questions. The data analysis technique used was descriptive analysis, Prerequisite Analysis Test, namely Normality Test and Homogeneity Test, N-Gain Score Test, Wilcoxon Test, and Mann Whitney Test. Data processing used SPSS Version 22. The results showed an N-Gain Score of 0.27, G < 0.3 (low category). The results of hypothesis testing are: (1) There were differences in student learning outcomes before and after using the Problem-Solving method with a significance value of 0.002 < 0.005. (2) There was no difference in student learning outcomes before and after using the Recitation method with a significance value of 0.399 > 0.05. (3) There was no difference in student learning outcomes between those using the Problem Solving method and the Recitation method with a significance value of 0.435 > 0.05.